The Influence of Body Mass Composition on the Postural Characterization of School-Age Children and Adolescents. (14th October 2018) - Rusek, Wojciech; Baran, Joanna; Leszczak, Justyna; Adamczyk, Marzena; Weres, Aneta; Baran, Rafał; Inglot, Grzegorz; Pop, Teresa
Abstract : Introduction . In recent years a significant increase in the percentage of children with postural problems has been observed. It is necessary to focus on preventing the phenomenon and on analysis of existing postural defects. Aim . The aim of this work was to assess the potential relationship between body mass composition and body posture in school-age children. Material and Methods . 464 school-age children ranging from 6 to 16 years (234 boys and 230 girls) were qualified for the study. Body mass composition was assessed using the analyzer Tanita MC 780 MA . Assessment of body posture was performed using Zebris system. All the results were analyzed with statistical methods. The accepted level of significance was p<0.05. Results . Analyses of the disparities between the girls and the boys showed statistically significant differences in all of the body mass components and in obliquity of the pelvis/shoulder. The boys were characterized by higher contents of muscle tissue ( p <0.001), bone tissue ( p <0.001), fatless tissue ( p <0.001), and body water ( p <0.001) as well as a greater obliquity angle ( p =0.018). The girls, on the other hand, were found with higher content of fatty tissue ( p <0.001). The children with lower content of muscle tissue (p=0.030), fatless tissue (p=0.030), water (p=0.030), and higher content of fatty tissue measured in kg (p=0.027) were characterized by greater pelvic obliquity. Conclusion . The current study shows evidence that sex, as a strongly differentiating factor, determines body mass composition and the occurrence of suboptimal postures only in the pelvic area. Body mass composition differentiates body posture of the study group. The content of fatty tissue influences the occurrence of suboptimal postures in the scapula and pelvic area in the frontal plane. The content of muscle tissue is associated with faulty postures in the scapula and pelvic area in the frontal plane.